Latent autoimmune diabetes of adulthood (LADA) is associated with small fibre neuropathy. Issue 9 (4th March 2019) - Alam, U.; Jeziorska, M.; Petropoulos, I. N.; Pritchard, N.; Edwards, K.; Dehghani, C.; Srinivasan, S.; Asghar, O.; Ferdousi, M.; Ponirakis, G.; Marshall, A.; Boulton, A. J. M.; et al.
Abstract: Aim: To assess if latent autoimmune diabetes of adulthood (LADA) is associated with small fibre neuropathy. Methods: Participants with LADA (n=31), Type 2 diabetes (n=31) and healthy control participants without diabetes (n=31) underwent a detailed assessment of neurologic deficits, quantitative sensory testing, electrophysiology, skin biopsy and corneal confocal microscopy. Results: The groups were matched for age (healthy control without diabetes: 53.5±9.1 vs. Type 2 diabetes: 58.0±6.5 vs. LADA: 53.2±11.6 years), duration of diabetes (Type 2 diabetes: 10.0±8.3 vs. LADA: 11.0±9.1 years) and blood pressure. However, BMI ( P =0.01) and triglycerides ( P =0.0008) were lower and HbA1c ( P =0.0005), total cholesterol ( P =0.01) and HDL ( P =0.002) were higher in participants with LADA compared with Type 2 diabetes. Peroneal motor nerve conduction velocity ( P =0.04) and sural sensory nerve conduction velocity ( P =0.008) were lower in participants with latent autoimmune diabetes in adults compared with Type 2 diabetes. Intra‐epidermal nerve fibre density ( P =0.008), corneal nerve fibre density ( P =0.003) and corneal nerve branch density ( P =0.006) were significantly lower in participants with LADA compared with Type 2 diabetes. There were no significant differences in the other neuropathy parameters. Conclusions: Despite comparable age and duration of diabetes, participants with LADA demonstrate more severe neuropathy and particularly small fibre neuropathy, compared with participants with Type 2 diabetes. What's new?: Treatment inertia in latent autoimmune diabetes of adulthood (LADA) leads to a prolonged period of poor glycaemic control, which may lead to complications. We demonstrate an excess of small fibre neuropathy in a cohort of patients with LADA compared with age‐ and diabetes duration‐matched people with Type 2 diabetes. Small fibre neuropathy can be diagnosed comparably using corneal confocal microscopy or skin biopsy, further supporting the utility of corneal confocal microscopy as a valid method to screen for diabetic neuropathy in at risk populations.